Afraid but misinformed: Conspiracist beliefs cancel the positive influence of fear of COVID-19 on vaccination intentions - Findings from a Romanian sample - Holman, Andrei C.; Popușoi, Simona A. (Frontiers in Psychology, 2023)
Understanding the factors that make people more likely to refuse vaccination against COVID-19 is crucial in order to design public health messages efficient in increasing vaccination rates. As COVID-19 creates risks of seriously damaging health effects, fear of this disease is as a significant determinant of vaccination intentions, as indicated by past research. Nevertheless, this positive influence may be limited in people who do not consider vaccines as a solution to protect against COVID-19, especially those who hold conspiracist beliefs about the new coronavirus and, implicitly, about the newly developed vaccines. The present study examined in a cross-sectional design on a convenience sample (N=564) the joint effect of fear of COVID-19 and conspiracist beliefs on vaccination intentions, advancing past research on their independent influences. Furthermore, we investigated and controlled the effects of perceived risk of catching COVID-19, trust in medical experts, attitude towards vaccination and socio-demographical characteristics (i.e., gender, age, and education), previously found to be associated to COVID-19 vaccination intentions. We also tested the effect of ambivalence towards vaccination, i.e., the degree to which people simultaneously hold positive and negative evaluations of this intervention, as the widespread misinformation on the new coronavirus and its vaccines may induce ambivalence on this latter issue in many people. The results showed that the positive effect of fear of COVID-19 on vaccination intentions emerged only in participants who tend not to endorse conspiracist ideas on the new coronavirus. Moreover, higher vaccine hesitancy was found in participants with higher ambivalence towards vaccination, in those who perceive the risk of being contaminated by the new coronavirus as low, and in those with more negative attitudes towards vaccines in general. Vaccine ambivalence also emerged as a mediator of the negative effects of conspiracist beliefs about COVID-19 on vaccination intentions. This pattern of findings suggests the public messages emphasizing the risks of COVID-19 should also combat misinformation in order to maximize vaccine uptake.